Immunomodulatory and ameliorative effects of Lactobacillus and Saccharomyces based probiotics on pathological effects of eimeriasis in broilers. (January 2019) - Awais, Mian Muhammad; Jamal, Muhammad Asif; Akhtar, Masood; Hameed, Muhammad Raza; Anwar, Muhammad Irfan; Ullah, Muhammad Irfan
Abstract: Eimeria infection is very important in broilers and causes heavy economic losses in extensive farming system due to reduced weight gains, high mortality and poor feed conversion ratio (FCR). Under the circumstances, there is a dire need to devise effective control strategies to avoid/counteract this infectious threat. This study was conducted to assess the immunomodulatory and ameliorative effects of Lactobacillus and Saccharomyces based probiotics against Eimeria infection in broilers. The results showed statistically higher ( P <  0.05) lymphoproliferative responses in experimental groups treated either with Lactobacillus or Saccharomyces based probiotics, as compared to control group. Further higher antibody titers (geomean titers) were also recorded in chickens of experimental groups treated with probiotics as compared to those of control group. The probiotic treated groups also revealed significantly improved ( P <  0.05) FCRs as compared to control group. In challenge experiment, significantly lower ( P <  0.05) oocyst counts were recorded in broilers treated with probiotics, when compared with control group. Further, experimental groups also revealed significantly higher ( P <  0.05) daily weight gains and protection rates as compared to control. The data regarding the lesion scoring showed that chickens treated with probiotics had higher values of percent protection against intestinal and caecal lesion, when compared with those of control group. In conclusion, supplementation of probiotics proved very useful to enhance the immunological and performance potentials of broilers which subsequently provided protection against Eimeria infection. Further studies on the physico-chemical properties along with commercial feasibility and cost benefit analysis of these probiotic species are needed for wise selection to get maximum profit from broiler industry. Highlights: Lactobacillus and Saccharomyces based probiotics enhanced the natural immunity and feeding efficiency in broilers. Artificial infection with mixed Eimeria spp. in probiotics administered and control broilers. Decreased mortality, oocyst count and lesion scoring in broilers administered with probiotics. Higher weight gains and antibody titres against Eimeria spp. in broilers administered with probiotics.